Hydrazine Sensor Based on Co3O4/rGO/Carbon Cloth Electrochemical Electrode. Issue 12 (7th March 2016) - Wang, Qian; Wu, Meiyan; Meng, Shangjun; Zang, Xiaoxian; Dai, Ziyang; Si, Weili; Huang, Wei; Dong, Xiaochen
Abstract : Porous cobalt oxide (Co3 O4 ) nanosheets, vertically aligned on reduced graphene oxide (rGO) modified 3D carbon cloth (CC), are synthesized by using a facile diffusion method at room temperature following a thermal annealing process (named as Co3 O4 /rGO/CC). Employed as freestanding electrochemical electrode, the detection behaviors of the Co3 O4 /rGO/CC toward hydrazine have been systematically investigated. It exhibits a high sensitivity (1306.7 μA mM −1 cm −2 ), good stability, and excellent selectivity. The detection limit for hydrazine can reach to 0.141 × 10 −6 M with a linear response range of 5–470 × 10 −6 M. The outstanding sensing properties of the Co3 O4 /rGO/CC electrode can be attributed to the electrocatalytic activity of porous Co3 O4 nanosheets, the good conductivity of carbon cloth, and the large surface area of the 3D structure. It presents potential applications in the field of environment protection, food analysis, medicine, and so on. Abstract : Porous cobalt oxide nanosheets, veritcally aligned on reduced graphene oxide modified three‐dimensional carbon cloth, were synthesized by using a facile diffusion method at room temperature following a thermal annealing process. Employed as freestanding electrochemical electrode, the composite presents high sensitivity, good stability, and excellent selectivity for hydrazine detection.